2021
DOI: 10.1177/20503121211032813
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and anxiety in patients with chronic obstructive pulmonary disease and their association with psychosocial outcomes: A cross-sectional study from Pakistan

Abstract: Objectives: Chronic obstructive pulmonary disease contributes to substantial health and economic burden worldwide. Co-morbid depression and anxiety are highly prevalent in patients with chronic obstructive pulmonary disease. Depressive symptoms in chronic obstructive pulmonary disease are associated with poorer survival, longer hospitalisation and impaired quality of life. Literature on chronic obstructive pulmonary disease is largely derived from high-income countries; yet 90% of deaths related to chronic obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…Depression and anxiety are difficult to diagnose and treat in COPD patients because their symptoms frequently coincide with COPD symptoms [ 69 ]. COPD patients with co-occurring depression have been found to have higher levels of anxiety, less social support, higher social stress and more subjective impairment in quality of life than COPD patients without depression [ 70 ]. These findings emphasize the need to address individual’s history of mental illness to support the health of COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety are difficult to diagnose and treat in COPD patients because their symptoms frequently coincide with COPD symptoms [ 69 ]. COPD patients with co-occurring depression have been found to have higher levels of anxiety, less social support, higher social stress and more subjective impairment in quality of life than COPD patients without depression [ 70 ]. These findings emphasize the need to address individual’s history of mental illness to support the health of COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that anxiety and depression are common in COPD. COPD patients have a greater prevalence of depression and anxiety than unaffected persons [ 33 ] and are reported to have a higher relative risk of depression [ 34 ]. A large cross-sectional study (n = 4803) reported a higher rate of depression in patients with COPD (62.1%) than those with other chronic diseases [ 35 ].…”
Section: Comorbid Conditions Of Mood Disorders In Copdmentioning
confidence: 99%
“…These findings have been confirmed for LMICs as well. A cross-sectional study of 293 COPD patients attending outpatient clinic in Pakistan found that 51 and 20% of people reported depression and anxiety, respectively [18]. Those reporting breathlessness had significantly higher levels of depression and lower quality of life.…”
Section: Impact Of Chronic Respiratory Diseasesmentioning
confidence: 99%